Unraveling the record of a tropical continental Cretaceous-Paleogene boundary in northern Colombia, South America. (March 2022) - Parra, Felipe de la; Jaramillo, Carlos; Kaskes, Pim; Goderis, Steven; Claeys, Philippe; Villasante-Marcos, Víctor; Bayona, German; Hatsukawa, Yuichi; Caballero, Dayenari
Abstract: The Cretaceous-Paleogene (K-Pg) boundary event, triggered by the Chicxulub asteroid impact in Mexico ∼66 Myr ago, is recognized as one of the major environmental crises in Earth's history. Its effects on the evolution of tropical vegetation were drastic, giving rise to the closed-canopy tropical rainforest. Despite of its importance, the actual K-Pg boundary event layer has not yet been identified in terrestrial sections within tropical latitudes. Here, we study a sediment core (Diablito-1) from northern Colombia and described its lithofacies, palynostratigraphic content, magnetic susceptibility and geochemical composition, including the concentration of key elements linked to a meteoritic contribution such as iridium. We found an 8.2 cm-thick (0.27 inches) interval with gravel-size calcareous intraclasts, broken skeletal fragments and siliceous spherules that were transported during a short-duration high-energy event into the coastal plain. Very fine-to medium-grained spherules, concentrated in several layers of the flow structure, could be interpreted as derived from the K-Pg impact event. This thin intraclastic packstone interval lies within the extinction level of the palynomorph Echimonocolpites franciscoi, an important biostratigraphic event associated with the K-Pg boundary in Colombia. In addition, this layer is associated with both a small iridium anomaly and high concentration of several other major and trace elements that are occurring above a low Magnetic Susceptibility (MS) interval and within the initial phase of a high MS interval. These lines of evidence support the position of the K-Pg event layer within the thin interval that includes the spherules in the Diablito-1 core. Highlights: We identified a K-Pg boundary layer in terrestrial sediments of an neotropical site in Northern South America.